2014
DOI: 10.1016/j.immuni.2014.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Transcriptional Basis of CD4+ T Cell Dysfunction during Chronic Infection

Abstract: Summary T cell exhaustion is common during chronic infections. While CD4+ T cells are critical for controlling viral load during chronic viral infections, less is known about their differentiation and transcriptional program. We defined the phenotypic, functional and molecular profiles of exhausted CD4+ T cells. Global transcriptional analysis demonstrated a molecular profile distinct from effector or memory CD4+ T cells and also from exhausted CD8+ T cells, though some common features of CD4+ and CD8+ T cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
527
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 440 publications
(556 citation statements)
references
References 44 publications
27
527
0
2
Order By: Relevance
“…This dysfunctional state is also associated with a pattern of transcription factor expression distinct from those of functional effector or memory T cells. 7,8,23,24,34 Functional exhaustion of CD8 C T cells is also observed in cancers and is associated with co-expression of PD-1 and Tim-3 15,16 However, exhaustion of CD4 C effector T cells in cancer is still not well defined. In the cohort of HNSCC patients, we have studied sorted PD-1 hi Tim-3 ¡ and PD-1 C Tim-3 C CD8 C TIL manifested exhausted phenotypes with defective Th1 cytokine production and proliferation (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…This dysfunctional state is also associated with a pattern of transcription factor expression distinct from those of functional effector or memory T cells. 7,8,23,24,34 Functional exhaustion of CD8 C T cells is also observed in cancers and is associated with co-expression of PD-1 and Tim-3 15,16 However, exhaustion of CD4 C effector T cells in cancer is still not well defined. In the cohort of HNSCC patients, we have studied sorted PD-1 hi Tim-3 ¡ and PD-1 C Tim-3 C CD8 C TIL manifested exhausted phenotypes with defective Th1 cytokine production and proliferation (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Infection and Immunity previously published study of gene expression in CD4 ϩ T cells following LCMV infection (17) and found that of genes significantly upregulated in wild-type CD4 ϩ T cells following Plasmodium infection, compared with uninfected controls, there were 13 genes shared by these two data sets, including two well-characterized exhaustionassociated genes, Lag-3 and Maf (Fig. 4C).…”
Section: Resultsmentioning
confidence: 82%
“…Several recent studies have reported characterization the patterns of gene expression that define exhaustion in CD4 ϩ and CD8 ϩ T cells. These studies have identified genes that comprise a specific gene expression program that shows marked differences from genes activated in other processes of T cell inactivation, such as T cell anergy (17,18). These genes encode inhibitory receptors, such as PD-1, LAG-3, or CTLA-4, and genes involved in the regulation of different aspects of T cell biology, including apoptosis, cell metabolism, control of cytokine expression, and cell-to-cell communication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although persistent LCMV infection is known to result from functional T cell exhaustion (reviewed in Ref. 181) associated with elevated PD-1 expression on T cells (182), as well as IL-10 and PD-L1 expression in infected mice (183,184), a role for type I IFNs in this process was poorly understood until recently.…”
Section: Lymphocytic Choriomeningitis Virusmentioning
confidence: 99%